Pyrimethamine sensitizes pituitary adenomas cells to temozolomide through cathepsin B‐dependent and caspase‐dependent apoptotic pathways. Issue 8 (13th June 2013) - Dai, Congxin; Zhang, Bo; Liu, Xiaohai; Guo, Kai; Ma, Sihai; Cai, Feng; Yang, Yakun; Yao, Yong; Feng, Ming; Bao, Xinjie; Deng, Kan; Jiao, Yonghui; et al.
<x xml:space="preserve">Abstract</x> Invasive pituitary adenomas (PAs) are generally refractory to conventional therapy and salvage treatment with temozolomide (TMZ). In addition to antiprotozoan effects, pyrimethamine (PYR) has recently shown its strong antitumor activity as an antineoplastic agent or in combination with TMZ in metastatic melanoma cells. In this study, the effects of TMZ, PYR or TMZ/PYR combination on rat/mouse PA cell lines αT3‐1, GH3, MMQ and ATt‐20 as well as GH3 xenograft tumor model were evaluated. TMZ/PYR combination synergistically inhibited proliferation, invasion and induced apoptosis of these PA cell lines in vitro. Strikingly, combination treatment with TMZ and PYR produced synergistic antitumor activity and enhanced the survival rate of GH3 xenograft tumor models without increasing systemic side effects. In addition, TMZ/PYR induced cell cycle arrest, increased DNA damage, upregulated the expression of cathepsin B, BAX, cleaved PARP and phosphorylated histone H2AX as well as elevated caspase3/7, 8 and 9 activities. The decreased expression of Bcl‐2, MMP‐2 and MMP‐9 alone with cytochrome c release from mitochondria into the cytosol was also observed in the TMZ/PYR combination group. The increase in cell apoptosis due to combination with PYR was rescued by leucovorin. These data suggest that PYR may enhance the efficacy of TMZ via triggering both cathepsin B‐dependent and caspase‐dependent apoptotic pathways. Therefore, combination of PYR and TMZ may provide a novel regimen for invasive PAs refractory to standard therapy and TMZ.